Towards a uniform European legal framework in the prevention of risks and civil liability in the field of intelligent automated driving - Núñez Zorrilla, Mª Carmen (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Worldwide, we are moving towards fully automated or autonomous intelligent transport systems, by means of which we want to combat greenhouse gas emissions, air, noise and water pollution, traffic accidents, congestion and the loss of biodiversity. Hence, the concern for the development, from the European Union, of a legal framework for the prevention of risks and the regulation of civil liability derived from the damage that these systems may cause, since the specific characteristics that define this technology create new risks that are not adequately covered by traditional regulations, which must be reviewed to adapt to new technologies with artificial intelligence.